Pengetahuan geografi masyarakat Sunda berdasarkan manuskrip Sunda kuno dan catatan perjalanan orang Portugis - Hedi S. Ekadjati, (Universiti Kebangsaan Malaysia, 2007)
The Old Sundanese manuscripts are those written on palm leaf and contain matters related to pre-Islamic Sundanese culture. They were written in old Sundanese or old Javanese character and language. Four of such manuscripts, with the youngest one written in the end of 16th century contained not only many geographical data of Sunda, but also other places in Asia. Are the geographical data of historical value or merely creation from the authors? They are found to contain historical truth after comparing them with the three descriptions of voyages of the contemporary Portuguese travelers